2012
DOI: 10.1682/jrrd.2011.03.0051
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric study of the Neurobehavioral Symptom Inventory

Abstract: Abstract-The Department of Veterans Affairs (VA) uses the Neurobehavioral Symptom Inventory (NSI) to measure postconcussive symptoms in its comprehensive traumatic brain injury (TBI) evaluation. This study examined the NSI's item properties, internal consistency, and external validity. Data were obtained from a federally funded study of the experiences of combat veterans. Participants included 500 Operations Iraqi and Enduring Freedom veterans, 219 of whom sustained at least one TBI. Data were collected at fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
119
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(124 citation statements)
references
References 19 publications
5
119
0
Order By: Relevance
“…15 In the present study, TBI participants reported a greater number of post-concussive symptoms based on NSI total scores, which is consistent with the prior TBI literature. 49,50 Further, the area of significant cortical thinning in the TBI population positively correlated with NSI scores, suggesting that post-concussive symptoms are related to right frontotemporal dysfunction. However, the NSI scale is not specific to TBI, since individuals with affective disorders (i.e.…”
Section: Discussionmentioning
confidence: 91%
“…15 In the present study, TBI participants reported a greater number of post-concussive symptoms based on NSI total scores, which is consistent with the prior TBI literature. 49,50 Further, the area of significant cortical thinning in the TBI population positively correlated with NSI scores, suggesting that post-concussive symptoms are related to right frontotemporal dysfunction. However, the NSI scale is not specific to TBI, since individuals with affective disorders (i.e.…”
Section: Discussionmentioning
confidence: 91%
“…A cut-score of 17.5, described by King, was used to indicate clinical significance of total scores. 48 Previous studies indicate that the NSI has good psychometric properties. 28 Other measures.…”
Section: Cognitive Performance Measuresmentioning
confidence: 99%
“…It has high internal consistency (total α = .95; subscale α = .88-.92) and reliability (r = 0.88-0.93). 17 Symptoms of PTSD were assessed by the PTSD…”
Section: Determination Of Pcd Ptsd and Depression Symptomsmentioning
confidence: 99%